Understanding crucial factors in cultured meat production: A comprehensive SWOT analysis - Farzana Choudhary; S.A. Khandi; Rana Muhammad Aadil; Abdo Hassoun; Alaa El-Din A. Bekhit; Gholamreza Abdi; Zuhaib F. Bhat (Applied Food Research)
The objective of the present study was to identify the main strengths, weaknesses, opportunities and threats (SWOT) associated with cultured meat production to increase awareness about the crucial factors that can potentially affect the growth and development of this industry. A SWOT analysis was performed using food science scholars (n = 250) and veterinary professionals (n = 150) as the respondents using an interview schedule and a questionnaire in the form of a Google form was used for meat scientists (n = 50). Being related to the field of meat and food production, their opinion is of paramount importance. Most of the respondents were male (70.0 %, 64.67 %, and 51.20 % for meat scientists, veterinary professionals, and food scholars, respectively) who ate meat as a part of their regular diet (86.0 %, 79.25 %, and 61.25 %, respectively) and perceived cultured meat as unnatural. The ‘skilled human resources’ (80.85 % of meat scientists), ‘available knowledge in the field’ (66.60 % of veterinary professionals), and ‘low carbon footprint’ (63.04 % of food scholars) were perceived as the main strengths. The meat scientists (93.33 %) and veterinary professionals (78.0 %) perceived ‘small-scale and high-cost of production’ as the main weakness. Also, meat scientists (93.33 %) perceived the ‘sophisticated nature of the technology’ and food scholars (61.20 %) considered ‘funding for further research’ as a major weakness. Both the meat scientists (87.23 %) and veterinary professionals (83.30 %) perceived ‘high demand for meat products’ whereas food scholars (61.20 %) considered ‘lower use of land and water’ as the major opportunity. Both the meat scientists (91.30 %) and food scholars (72.0 %) perceived a ‘lack of information about consumer acceptance’ whereas veterinary professionals (74.60 %) considered ‘oligopolistic markets’ as the major threat. Our results have led to a better understanding of various crucial factors related to cultured meat. This can help to develop the right strategic planning and take proactive measures to mitigate the impact of threats and weaknesses. Right strategic planning and proactive measures can have a pivotal role in the social acceptance and the future expansion of this industry.